From Antibodies to Immunity: Assessing Correlates of Flavivirus Protection and Cross-Reactivity - Hannah E. Flores; Eduar Fernando Pinzon Burgos; Sigrid Camacho Ortega; Alonso Heredia; Joel V. Chua (Vaccines)
Flaviviruses are arthropod-borne RNA viruses that can cause a wide range of human diseases, from mild symptoms to severe illness with multiorgan failure and death. Effective prevention of these diseases relies on identifying reliable vaccine targets, typically measured by correlates of protection (CoPs), which help indicate host immunity after vaccination. Current vaccines primarily focus on neutralizing antibodies (nAbs) against the viral envelope E protein, though emerging evidence suggests other potential targets may also be effective in disease prevention. Additionally, there is growing evidence of cross-protection between different flaviviruses when immunity to one virus is achieved, although this can be limited by antibody-dependent enhancement. This review examines the current understanding of flavivirus immunity, CoPs, and the potential for cross-protection in the context of existing vaccine strategies.